The teachers’ conception of specialized educational service in multifunctional resource classrooms - Ferreira, Naidson Clayr Santos; Costa, Carolina Severino Lopes da (Revista Eletrônica de Educação, 2016)
<!–[if gte mso 9]> 1024x768 <![endif]–> <!–[if gte mso 9]> 1024x768 <![endif]–> The specialized educational service (SES) has been considered part of the inclusion process of special education target groupin the regular educational system. Guidelines of current Ministry of Education policy recommend that this service should be offered in multifuncional resource classrooms (MRC). With the purpose of getting to know better the characteristics of this service, this study aimed to describe and analyze some aspects of the SES offered in MCR in municipal schools of a midsize town localized in the southwest Bahia, Brazil. Data were collected using two instruments, the questionnaire to characterize the MRC’s teachers and the script of trigger questions about Teaching organization in the MRC and mainstream classrooms, also structured as a questionnaire. Data were analyzed using the thematic categorization technique of the content analysis. The results showed that the specialized teachers presented a positive conception about the SES work that can be developed in the MRC, however, they pointed out the importance of having adjustments, related to the resources available in the classrooms as well as to the school’s dynamic so that the student can be served in a way that fulfills his educational needs. They point to the importance of developing studies to cover the managers’ conceptions on this process, since some necessary changes involve managers’ decisions. Keywords: Special Education. Specialized educational services. Multifunction resource classrooms. Specialized teachers. <!–[endif] –> <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>